Pengaruh pH dan Tegangan Listrik dalam Elektrolisis Limbah Padat Baja (Slag Eaf) Sebagai Upaya Mereduksi Kandungan Logam Fe pada Limbah Padat Industri Galvanis - Abdul Aziz; Wirda Udaibah; Malikhatul Hidayah (Walisongo Journal of Chemistry, 2018)
Galvanization is a metal coating process that is widely used in industry. The effects of this metal coating process are not entirely beneficial to society. The issue of pollution generated by the metal coating activity becomes very important. The objective of this research is to reduce Fe metal content from solid waste steel using electrolysis process with variation of pH of electrolyte solution and voltage. This research uses experimental method with test of metal content composition using X-Ray Flouresence, and Fe metal reduction using electrolysis process. This research activity used stainless steel plate as cathode and solid steel waste chunk as anode. Variations of pH of FeSO4.7H2O electrolyte solution used during electrolysis process are pH = 2, pH = 2.5, pH = 3, pH = 3.5 and pH = 4. Variation of electric voltage used is 3 volts, 6 volts, 9 volts and 12 volts. The result of purity level analysis of the initial Fe metal at anode was 84,48 %, while after electrolysis process there was an increase of metal purity attached to the cathode of 96,58 %. The result showed that the effect of pH variation of the electrolyte solution on the mass produced in the electrolysis process in the A1, A2, A3, A4 and A5 samples was 0,09; 0,07; 0,02; 0,02; and 0,02 g. The greater the concentration of H+ of the electrolyte solution the more mass produced. In variable voltage of electricity on samples A11, A21, and A31 mass produced that is equal to 0,14; 0,13; and 0,10 g. While the mass of A41 sample did not increase in the cathode produced during the electrolysis process. The greater the voltage used in the electrolysis process the greater the mass produced.